P27 Depletion of cardiac succinate mediates impaired hypoxia-inducible factor 1Α signalling by long chain fatty acids in insulin resistance. (21st March 2018) - Dodd, MS; Sousa Fialho, Mdl; Montes Aparico, CN; Kerr, M; Timm, KN; Griffin, JL; Luiken, JJFP; Glatz, JFC; Tyler, DJ; Heather, LC
Abstract : Hypoxia-inducible factor (HIF)1α is activated following myocardial infarction, and is critical for cell survival in hypoxia. In cancer, changes in Krebs cycle intermediates have also been shown to affect HIF1α stabilisation. We questioned whether abnormal metabolism could prevent HIF1α activation in diabetes. Type 2 diabetic hearts have decreased HIF1α protein accumulation in ischemia, which correlated negatively with plasma fatty acid (FA) concentrations and positively with myocardial succinate concentrations. In insulin-resistant cardiomyocytes, HIF signalling and downstream metabolic adaptation was suppressed in hypoxia. Impaired HIF1α stabilisation was due to increased degradation of the protein in hypoxia, as inhibition of the proteasome or inhibition of the HIF hydroxylases was able to increase HIF1α in insulin resistance. This was due to abnormal metabolism, as FA (both palmitate and oleate) prevented HIF1α accumulation in a concentration-dependent manner, which could be reversed by blocking CD36 mediated FA uptake. Succinate promotes HIF stabilisation by inhibiting the HIF hydroxylases, however, FA suppressed succinate accumulation during hypoxia. Increasing succinate concentrations using dimethylfumarate, overrides the FA-mediated inhibition of HIF1α in a concentration-dependent manner. Pharmacologically inhibiting the HIF hydroxylases promoted HIF1α accumulation and improved cardiac function following ischemia-reperfusion in diabetic rats. In conclusion, elevated FA in type 2 diabetes prevent HIF1α accumulation by decreasing succinate concentrations in hypoxia.